Postjunctional Origin of the indirect-like sympathomimetic effect of metanephrine and normetanephrine on blood pressure (Revista Española de Fisiología, 1984)
The effects of metanephrine and normetanephrine have been compared with those from equiactive doses of the origin compounds, adrenaline and noradrenaline, on the pressor responses in rat, in order to determine whether their effects are owed, at least partially, to a releasing presynaptic action of the catecholamines in normal animals as well as those pretreated with reserpine, guanethidine and 6-OH-dopamine.Their effects have likewise been studied in isolated perfused renal arteries both in normal and reserpinized rats.None of the adrenolytic agent used were able either to reduce the duration of the hypertensive response or to accelerate tachyphylaxis.Identical results were obtained in renal artery preparations.It is thus concluded that the catecholamines stored in presynaptic endings are not involved in the observed phenomena and it is suggested that they might depend on the high doses required to produce effects equiactive to those of the origin substances.